Intelektwalisasyon ng pilosopiyang Filipino - Timbreza, Florentino T. (Malate, Maynila, Pilipinas De la Salle University Press, 1999)
Understanding the Filipino philosophy.
Includes bibliographical references (p. 227-230).
Keywords: Philosophy, Filipino